Konteksty oraz uwarunkowania ruchu separatystycznego we wschodnim regionie Ukrainy w 2014 roku - Gladii, Andrzej (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In this paper was taken an attempt to research the causes of separatism in the Donbass based on a multi-faceted inquiry. Donbass has always been a key region in Ukraine. In many cases here were decided the political and economic destiny of the state. This region is the most socially and economically diversified. Donbass is a place of the most dangerous working conditions and the enormous social inequalities in Ukraine. In 2014 after the events at the Euromaidan Donbass was a field of fighting between the Ukrainian government and Russian-backed separatists. The issue of separatism in Ukraine remains unresolved.